Mine closure residual risk management: identifying and managing credible failure modes for tailings and mine waste - Sanders, J.; McLeod, H.; Small, A.; Strachotta, C. (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
Closure planning relies on a solid understanding of risk management. With tailings and other mine waste facilities representing a significant life-of-mine (LoM) liability associated with the mining industry, a proper understanding and management of residual risk at closure is fundamental to implementing a mine closure plan that will be considered successful. Having a comprehensive technical basis of the triggering events and credible failure modes after closure that may impact receptors and prohibit meeting closure objectives is crucial. Performance evaluation and success criteria can then be properly developed and assessed against closure objectives and obligations. In the wake of the recent Mount Polley, Fundão and Brumadinho mine tailings disasters, we are reminded that decisions made, past and present, affect the social acceptability of the industry in the future. The physical stability mechanisms that caused these tailings dam failures to occur can be present throughout the LoM into post-closure and represent an unacceptable long-term risk to society and the mine owner. Existing and closed facilities will still require post-closure stewardship to ensure protection of life, property and the environment regardless of future improved tailings technologies for new projects. Risk assessment can be a valuable tool for providing insight to the safety of a tailings facility and educating the mine closure planning team. Risk assessments should be conducted at each phase of a mine life, from design to closure, and are often undertaken. However, the authors of this paper have identified several challenges with risk assessments and, in this paper, have provided several recommendations to improve risk assessments for dam safety. We have built upon the guidance provided by ISO 3100:2018 on risk management. With this foundation established, the paper then discusses some of the unique challenges and relevant case studies associated with risk assessments for closure residual risk. If the risk assessments conducted during design and operation are flawed, then the risk assessment for the closure residual risk will have reduced value.